ANALISIS FRAMING PEMBERITAAN KASUS DUGAAN PENISTAAN AGAMA BASUKI TJAHAJA PURNAMA DI MEDIA ONLINE KOMPAS.COM DAN HIDAYATULLAH.COM - Fery Rohmadi; Maya Sekar Wangi Siswanta (Solidaritas, 2017)
ANALISIS FRAMING PEMBERITAAN KASUS DUGAAN PENISTAAN AGAMA BASUKI TJAHAJA PURNAMA DI MEDIA ONLINE KOMPAS.COM DAN HIDAYATULLAH.COM (TANGGAL 7 OKTOBER 2016 SAMPAI DENGAN 14 DESEMBER 2016)Oleh :Fery RohmadiMaya Sekar WangiSiswanta ABSTRACTThis study aims to describe frame comparison of cases of alleged blasphemy of Basuki Tjahaja Purnama or Ahok after the reporting of religious defamation case until the first trial in online media Kompas.com and Hidayatullah.com. The type of research used in this study is descriptive qualitative. This study aims to describe frame comparison of cases of alleged blasphemy of Basuki Tjahaja Purnama or Ahok after the reporting of religious defamation until the first trial. Data collection techniques use the completion stage, the data analysis phase, and the interpretation stage. And data analysis techniques use framing analysis model of Zhong and Pan framework and Gerald M. Kosicki. The result of this research is Kompas.com framing the news with attempts to try to build public opinion that Ahok is not necessarily guilty, and by presenting the expert statement which convey that Ahok's statement is not included in an act of defaming religion by presenting the news of Ahok. While Hidayatullah.com framing the news with an attempt to give a statement and lead the public opinion that what has been done Ahok is a blasphemy act, by presenting sources from the reporting party.Keywords: framing analysis, Pan and Kosicki, alleged blasphemy case Basuki Tjahaja Purnama or Ahok, Kompas.com and Hidayatullah.com